Comparison of the Effectiveness of Mindfulness-Based Therapy and Emotion-Focused Therapy on Pain Perception in Patients with Cardiovascular Diseases - Siavash Abkenar, Maryam; Seirafi, Mohammad Reza; Moraveji, Mahtab; Sabet, Mehrdad (Mental Health and Lifestyle Journal, 2026)
The aim of this study was to compare the effectiveness of mindfulness-based therapy and emotion-focused therapy on pain perception in patients with cardiovascular diseases. This study employed a quasi-experimental design with a pre-test–post-test control group structure. The statistical population consisted of patients with coronary artery disease (CAD) who referred to a specialized heart clinic in Rasht, Iran, during the first quarter of 2025. Sixty eligible participants were selected through purposive sampling and randomly assigned to three groups: mindfulness-based therapy, emotion-focused therapy, and a control group. The interventions were conducted over nine weekly sessions, while the control group received only routine medical care. Data were collected using the McGill Pain Questionnaire, which measures total, sensory, affective, evaluative, and miscellaneous pain perception. Data analysis was performed using descriptive statistics, repeated measures ANOVA, and Bonferroni and Tukey post-hoc tests with SPSS version 26. The results of the repeated measures ANOVA indicated significant main effects of time and group on total pain perception (F = 14.25, p < 0.001, η² = 0.20) and on the sensory (F = 9.87, p = 0.003), affective (F = 8.45, p = 0.005), and evaluative (F = 11.32, p = 0.001) subdimensions of pain. Bonferroni post-hoc tests confirmed significant reductions in total pain scores in both the mindfulness-based (ΔM = 7.59, p = 0.001) and emotion-focused (ΔM = 8.10, p < 0.001) experimental groups compared to pre-test values, whereas no significant changes were found in control groups. Tukey comparisons showed no significant difference between the two therapies (p = 0.623), indicating comparable effectiveness. Both mindfulness-based and emotion-focused therapies significantly reduced pain perception in patients with cardiovascular diseases, demonstrating equivalent effectiveness in modulating sensory, affective, and evaluative dimensions of pain through cognitive and emotional regulation mechanisms.